Genetic Differentiation by Nucleic Acid Homology I. Relationships Among Mycoplasma Species of Man - Reich, Paul R. (1966)
Reich, Paul R. (National Institutes of Health, Bethesda, Md.), Norman L. Somerson, Carol J. Hybner, Robert M. Chanock, and Sherman M. Weissman. Genetic differentiation by nucleic acid homology. I. Relationships among Mycoplasma species of man. J. Bacteriol. 92:302-310. 1966.—Genetic relatedness among human mycoplasmas was evaluated by measuring the amount of nucleic acid hybrid retained on a membrane filter. Hybrids were formed from deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) derived from representative strains of seven serologically distinct human Mycoplasma species. The results indicate that serologically distinct human Mycoplasma species can also be distinguished by the homology techniques. Low-level cross-reactivity was observed among nucleic acids derived from the seven species. Genetic heterogeneity was demonstrated among three strains of M. salivarium and between two strains of M. orale type 2. In contrast, comparison of three strains and three passage levels of M. pneumoniae revealed them to be indistinguishable. M. pneumoniae appears to be the most distinct of all human mycoplasmas, as shown by both homology and the high buoyant density value of its DNA. Nucleic acids from mycoplasmas which had identical buoyant densities were in some cases differentiable. Mycoplasmas with different DNA buoyant densities were invariably distinguishable by the homology technique.